Human rights and gender based violence in Asia : a comparative critical analysis - Lone, Fozia Nazir; Zhu, Guobin; Carty, Anthony (Routledge research in human rights law., 2026)
This edited book adopts a prescriptive and culturally relative narrative to understandand critique human rights within Asia. Simultaneously, it aims to understand howhuman rights, especially, such as women's rights, are practised and protected byAsian nations.The book evaluates the realisation of Eurocentric human rights by Asian states in linewith their domestic needs and priorities. It delineates the alien nature of westernstandards of human rights for Asia. Contributors focus on varied geographicalcontexts including South Asia, China, and Vietnam. The chapters also cover theprotection of women's rights in conflict zones in Myanmar, Kashmir and Afghanistan,as well as regional human rights mechanisms.Covering a diverse region, this book will be of interest to researchers and students ofinternational human rights, feminism and gender studies, particularly in the Asiancontext.